Experimental and Numerical Investigations on Flexural Behaviour of Prestressed Textile Reinforced Concrete Slabs - Dang Quang Ngo; Huy Cuong Nguyen (Salehan Institute of Higher Education, 2021)
Nowadays, concrete is mostly prestressed with steel. But the application of prestressing steel is restricted in a highly corrosive environment area due to corrosion of prestressing steel, leading to a reduction in strength and may cause sudden failure. Carbon textile is considered an alternate material due to its corrosive resistance property, high tensile strength, and perfectly elastic. Prestressing is also the only realistic way to utilize fully ultra-high tensile strength in carbon textile material. In this study, experimental and numerical analyses were carried out for the flexural behaviour of prestressed and non-prestressed carbon textile reinforced concrete slabs. This study also focuses on the inﬂuences of textile reinforcement ratios, prestressing grades on the flexural behaviour of carbon textile reinforced concrete (TRC). Fifteen precast TRC slabs were tested, of which six were prestressed to various levels with carbon textile. The obtained results show that prestressing textile reinforcement results in a higher load-bearing capacity, stiffness, and crack resistance for TRC slabs. The ﬁrst-crack load of the prestressed specimens increased by about 85% compared with those of non-prestressed slabs. Three-dimensional finite element models were developed to provide a reliable estimation of global and local response. The modeling techniques accurately reproduced the experimental behaviour. Doi: 10.28991/cej-2021-03091712 Full Text: PDF